The p53 family reaches the final frontier: the variegated regulation of the dark matter of the genome by the p53 family in cancer. Issue 11 (1st November 2020) - Napoli, Marco; Flores, Elsa R.
ABSTRACT: The tumour suppressor p53 and its paralogues, p63 and p73, are essential to maintain cellular homoeostasis and the integrity of the cell's genetic material, thus meriting the title of 'guardians of the genome'. The p53 family members are transcription factors and fulfill their activities by controlling the expression of protein-coding and non-coding genes. Here, we review how the latter group transcended from the 'dark matter' of the transcriptome, providing unexpected and intriguing anti-cancer therapeutic strategies.